A REVIS ED UNDERSTANDING OF ENGINEERING PROG NOSTICS - Tangkuman, Stenly (Jurnal Tekno Mesin, 2021)
Much of the understanding of prognostics currently appeared is scattered among many publication . Actually, m ost researchers have developed their own understanding of prognostics , and there are some divergences in literature . Firstly, t his work reviews the qualified publication that explain ed their understanding about prognostics in engineering application. Then, this paper has been prepared a revi sed understanding of engineering prognostics. However, it is hoped that this paper will provide the researchers with alternative prognostics’s under standing in use, and will be convenient when prognostics problem have to be solved. Keywords: prognostics, failure